Healthy Start—Départ Santé: A pilot study of a multilevel intervention to increase physical activity, fundamental movement skills and healthy eating in rural childcare centres - Chow, Amanda Froehlich (Can J Public Health, 2016)
OBJECTIVES: In order to improve healthy behaviours among rural children in their early years, a physical activity and healthy eating intervention (Healthy Start–Départ Santé) was implemented in rural childcare centres throughout Saskatchewan. The objective of the current study was to evaluate the impact of a multimodal physical activity and healthy eating intervention on educators’ provision of opportunities for children to improve their physical activity levels, fundamental movement skills and healthy eating behaviours. SETTINGS: Six childcare centres (three Francophone and three Anglophone) located in five different rural and semi-rural communities in Saskatchewan participated in this intervention. PARTICIPANTS: A total of 69 children with a mean age of 4 years 9 months, and 19 female early childhood educators. INTERVENTION: Guided by an ecological framework, we implemented a population health controlled intervention, using a wait list control design (48 weeks delayed intervention), and evaluated its impact in rural childcare centres. Mixed methods were employed to determine the effectiveness of the intervention. OUTCOMES: Overall, educators felt that the intervention supported the provision of physical activity and healthy eating opportunities for children. Increases in children’s physical activity levels were reported following the intervention. CONCLUSION: The lessons learned in this study can be used to improve the Healthy Start–Départ Santé intervention so that its implementation can be effectively expanded to childcare centres within and outside Saskatchewan, in turn, supporting the healthy development of early years (0–5) children in the province and beyond.